(untitled) (Shiksha Shastra Saurabh, 2025)
The COVID-19 pandemic accelerated the global transition of higher education institutions to digital and blended learning. This study discusses the use of blended learning in Bachelor of Computer Applications (BCA) Department at Kathmandu Shiksha Campus (KSC. Forty Students was involved in online survey while five faculty members were participated in mixed method of data collection through interviews. The analysis was done on Moodle Learning Management System (MLMS) of Kathmandu Shiksha Campus and the results show that it has improved teaching and learning with the help of its features such as video based learning, easy access to materials, availability of resources in time and encouraging students study in their flexible hours. Teachers are happy with the regular training session that college is conducting yet focused on more advanced workshops or research seminars. As per the findings, KSC’s blended learning program has been successful since its availability, students are more keen to learn, digital advancements are ongoing and teacher student interaction has been improved.